CCD OBSERVATIONS OF DL DRA - Udovichenko, S. N.; Yushchenko, A. V. (Одеські астрономічні публікації, 2017)
The CCD V-band photometry of variable Delta Sct-type star DL Dra have been carried out with aid of 0.5-m telescope-reflector. A CCD camera contains the Virtual-phase CCD-chip lSDOl5A. The light variation curves and power spectra are presented.